PENGEMBANGAN KEGIATAN WISATA PADA PRODUK WELLNESS TOURISM DI TAMAN WISATA ALAM GUNUNG PANCAR SENTUL KABUPATEN BOGOR - Ni Made Sri Puspa Dewi Roels; Ansel Anandya Patmadiwiria (Fakultas Pariwisata Universitas Pancasila, 2022)
Mount Pancar Nature Park is located in the Sentul area, Bogor Regency, West Java. This tourist attraction has natural tourism potential which is very suitable as a location for health tourism. The purpose of this study was to examine the potential for nature tourism. The development of Wellness Tourism can be a choice of new activities besides just enjoying nature tourism in tourist attractions. Methods of data collection are done by observation, interviews, literature study, and documentation. Determining informants using purposive sampling and accidental sampling by conducting in-depth interviews with managers and visitors with an amount of thirty people. The data obtained were analyzed using an interactive model. The results of this study are the potential for nature tourism in the Gunung Pancar Nature Tourism Park in the form of pine forests, open natural areas, and paths for sports activities. Wellness Tourism activities are divided into four categories, namely: mind mental activity or education in the form of activities to open mind-body therapy training, health nutrition or diet in the form of serving healthy food from places to eat, body physical fitness or treatment beauty in the form of cycling sports, open aerobics classes in nature and jogging, and relaxation rest or meditation, namely doing yoga activities.